Public Motivation: Motivasi Spiritual Gaya Baru (Studi Deskriptif pada Motivator Muda Reno di Lembaga Internusa) - Cut Irda Irda Puspitasari (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2020)
The purpose of this journal article is look at the motivation that was built by motivators in alluding to spiritual motivation in a new style through public motivation. The importance of motivation in this millennial era as the fulfillment of secondary human needs in the spiritual dimension that is trapped in the modernity of the world. This research was conducted by observing the Tarhib Ramadhan activities in the PDHI Wonosari building, Gunung Kidul with in-depth interviews with young motivator Reno and training participants. The result and discussion show that the rhetoric of public motivation with a new style, both through face to facr and online, has an effect on the general public, which can be seen from his enthusiasm in participacing in training, even though he has to pay.